Diseñar formaciones que faciliten el surgimiento de nuevas significaciones frente a acontecimientos inéditos y críticos - Simon Flandin; Deli Salini; Artemis Drakos; Germain Poizat (Universidade do Porto, 2020)
In this research, training situations are thought as opportunities to perturb/relaunch the participants' dynamics of meaning. Our contribution aims to (i) improve the conceptualization of training situations that are thought as aids to the understanding and transformation of the participants situations, and (ii) derive cross-cutting design principles that allow the enactment of these training situations in different contexts. We rely on the analysis of training programs aiming at either the management or the overcoming of events experienced as unprecedented and critical by the individuals at stake. The design principles of these training programs and their effects are analyzed with the conceptual tools developed within the course-of-action, integrating two additional dimensions: fictional and event-driven. The contribution to course-of-action program and to research on adult education is discussed through the perspective of the hypothesis of activity-sign.